THE LOSS OF SMELL (ANOSMIA) IN COVID 19 PATIENTS-TO WHAT EXTENT IT HELPS IN THE DIAGNOSIS OF COVID 19 AND FACTORS INFLUENCING ITS RECOVERY-A CLINICAL STUDY - UDAY SRIKAR, V SANJEEV; NAGA SWARNA, YELLETI VENKATA; YUGANDHAR, GANDUPALLI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: COVID-19 outbreak is a major pandemic affecting many people worldwide, including India. The main clinical features of this disease are cough, fever, and myalgia, and in some cases, breathing difficulty. There are many non-specific symptoms also. Loss of smell (Anosmia) is one of the non-specific clinical features in many patients. The main objective of this study is to diagnose COVID-19 disease in patients presenting with loss of smell, which helps in early isolation of the patient and prevents the spread of infection to others before the diagnosis of COVID-19 is confirmed by RTPCR, which may take 2–3 days. Another objective of this study is to know the factors that influence recovery from anosmia. Methods: Data was collected from 105 patients who attended Outpatient Department/COVID Ward in GITAM Institute of Medical Sciences and Research, Rushikonda, Visakhapatnam, from April 2020 to August 2020. The follow-up study for factors influencing the recovery of anosmia was performed in 100 patients who tested positive for COVID-19 disease with loss of smell as a presenting feature. Results: Male, to female ratio of patients with upper respiratory infection and loss of smell was 64:36. Out of 105 patients, 27 were tested positive for COVID19. Thus, the prevalence of anosmia in COVID 19 patients was 28.35%. In the follow-up study, out of 100 patients, 34 patients showed complete recovery in 2 weeks, and 42 patients showed partial recovery in 2 weeks and complete recovery in 4 weeks, and 24 patients showed only partial or no recovery within 1 month from the onset of anosmia. Conclusions: The presence of anosmia can be considered as a non-specific clinical feature in COVID-19, and early identification and isolation of the patient will help in decreasing the spread of disease to other people before the COVID-19 diagnosis is confirmed. It also suggests that recovery from loss of smell is better in middle-aged and female patients. The recovery has been delayed in patients with comorbidities and older people.